Ex vivo and in vitro assessment of anti-inflammatory activity of seed β-conglutin proteins from Lupinus angustifolius. (January 2018) - Lima-Cabello, Elena; Morales-Santana, Sonia; Foley, Rhonda C.; Melser, Su; Alché, Victor; Siddique, Kadambot H.M.; Singh, Karam B.; Alché, Juan D.; Jimenez-Lopez, Jose C.
Highlights: Narrow-leafed lupin β-conglutins are newly identified anti-inflammatory proteins. β1, β3, and β6 conglutins inhibit the production of NO and expression of iNOS. β-conglutins inhibit cytokines, chemokine CCL5, and CCR2 receptor expression. Conglutin isoforms β1, β3, and β6 may be potential anti-inflammatory agents. β-conglutin may help to prevent and treat chronic inflammation diseases. Abstract: The development of functional food ingredients using legume seed proteins has potential for nutraceutical use. We purified recombinant β-conglutin proteins (rβ1 to rβ4, and rβ6) from narrow-leafed lupin using affinity–chromatography, and evaluated their anti-inflammatory activity using ex vivo and in vitro systems. rβ1, rβ3, and rβ6 produced lower levels of pro-inflammatory mediators such as nitric oxide (about –34.0–fold in all cases), iNOS mRNA (−7.15, −7.97, −7.41–fold), interleukin 1β (−12.05, −11.64, −12.16–fold), chemokine CCL5 (−16.0, −18.0, −19.0–fold), and cytokines including TNF-α, INF-γ, IL-1β, IL-2, IL-6, IL-8, and IL-12 (β1: −28, −100, −8, −2, −49, −45, −127–fold; β3: −22, −400, −9, −3, −33, −10, −2.54–fold; β6: −72, −122, −11, −3, −2000, −13, −338–fold). These results suggest that the β1, β3, and β6 conglutins have potential as functional food components in nutraceuticals and that can provide alternative therapies for the prevention and treatment of inflammatory-related diseases.